Детский остров: [стихи и сказка] / Саша Черный ; художник В. Власов - Черный Саша (Библиотека школьника, 2012)
Экземпляры: (20180413) / Инвентарный номер: 40209 / Цена: 86.00 / Сис.шифр: Р2 / Авт.знак: Ч-49 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6